2000
DOI: 10.1046/j.1442-2042.2000.00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence among community‐dwelling people aged 40 years or older in Japan: Prevalence, risk factors, knowledge and self‐perception

Abstract: Background: Urinary incontinence (UI) is a common problem in adults, especially among the elderly. We examined the prevalence and risk factors of UI and potential factors hindering individuals from seeking treatment for UI among a community-dwelling population aged over 40 years. Methods: Data were collected by mailing a 23-item urinary incontinence questionnaire to a random sample of community-dwelling individuals aged 40-75 years (n = 3500) in seven towns of Shiga Prefecture, Japan. Collected data were then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
89
7
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(109 citation statements)
references
References 12 publications
6
89
7
7
Order By: Relevance
“…These findings were not similar to the study conducted by Kumari et al and Trupti N et al 14 These studies had shown higher incidence of stress urinary incontinence. Our study is different from other studies, may be due to difference in population studied.…”
Section: Discussioncontrasting
confidence: 57%
“…These findings were not similar to the study conducted by Kumari et al and Trupti N et al 14 These studies had shown higher incidence of stress urinary incontinence. Our study is different from other studies, may be due to difference in population studied.…”
Section: Discussioncontrasting
confidence: 57%
“…In Japan, it is reported that the prevalence of urinary incontinence among community-dwelling individuals aged 40–75 years in males and females was 10.5 and 53.7%, respectively [1]. Other studies revealed that the rate of urinary incontinence was 16.2% in males and 23.2% in females [2], or more than 50% of nursing home residents [3, 4]. In addition, urinary incontinence impairs the skin barrier function and finally induces skin breakdown [5].…”
Section: Introductionmentioning
confidence: 99%
“…17 Diabetes is theorized to be associated with early or accelerated aging and has been implicated in the pathogenesis of some geriatric conditions (e.g., falls). 4,9,12,14,15,17 There is no consensus regarding the definitions and understanding of the terms geriatric condition and geriatric syndrome. 1 Previous work by the authors investigated seven conditions -cognitive impairment, falls, incontinence, low body mass index, dizziness, vision impairment, and hearing impairment.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Geriatric conditions are associated with functional impairment in older adults and contribute to their complex health status. 1 Diabetes mellitus co-occurs with geriatric conditions in older adults, [4][5][6][7][8][9][10][11][12][13][14][15][16] and the American Geriatrics Society has included screening for and management of geriatric conditions (or syndromes) in its guidelines for improving the care of older adults with diabetes. 17 Diabetes is theorized to be associated with early or accelerated aging and has been implicated in the pathogenesis of some geriatric conditions (e.g., falls).…”
Section: Introduction Backgroundmentioning
confidence: 99%